Lipopolysaccharide stimulation test on cultured PBMCs assists the discrimination of cryopyrin-associated periodic syndrome from systemic juvenile idiopathic arthritis - Chao-Yi Wu (Nature Portfolio, 2021)
Abstract Systemic juvenile idiopathic arthritis (sJIA) and cryopyrin-associated periodic syndrome (CAPS) share many common manifestations. We aim to identify an applicable method to assist disease discrimination. Inflammatory cytokines were measured in the plasma of patients with CAPS, sJIA with persistent disease course and healthy controls. Supernatants collected from non-stimulated peripheral blood mononuclear cells (PBMCs) and those undergone inflammasome stimulation tests utilizing lipopolysaccharide (LPS) with and without adenosine triphosphate (ATP) were investigated. Inflammatory cytokines in patient plasma fail to differentiate sJIA from CAPS. PBMCs from sJIA secrets higher amount of IL-1β and IL-18 while CAPS PBMCs produces more caspase-1 without stimulation. IL-1β, IL-18, and caspase-1 were significantly elevated among CAPS PBMCs (all p < 0.05) upon LPS stimulation, but not when additional ATPs were provided. Levels of cytokines and PBMC responses to the stimulation assays were similar among all sJIA patients regardless of their history of macrophage activation syndrome. Unstimulated PBMC activities and the LPS inflammasome stimulation assay without exogenic ATPs can assist the differentiation of CAPS from sJIA with persistent disease course.